2009
DOI: 10.1177/000841740907600s06
|View full text |Cite
|
Sign up to set email alerts
|

Addressing pediatric wait times using the model of human performance technology

Abstract: The model of human performance technology provided a systematic approach with which to reveal the reason for extensive wait times for pediatric occupational therapy service. The model suggested a paradigm shift from a linear model of care to a continuum of care grounded in family-centred care. Implementation and evaluation of this new care model are ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Consistent with previous literature regarding the implementation of consultative models of service delivery (e.g., Bayona et al, 2006;Case-Smith & Cable, 1996;Spencer et al, 2006), therapists were concerned that it was not always enough to provide services that focused on building the capacity of teachers and changing the child's environment; rather, in certain situations, they felt that the provision of direct oneon-one interventions would have been more effective. Other authors have suggested that a continuum of services may be needed to manage the lengthy waitlists and varied needs of the school-aged population (Hanft & Shepherd, 2008;Hoyt-Hallett, Beckers, Enman, & Betuzzi, 2009). It is possible that there will be children whose needs cannot be fully managed via capacity building and environmental supports and who may require services outside of the classroom context.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous literature regarding the implementation of consultative models of service delivery (e.g., Bayona et al, 2006;Case-Smith & Cable, 1996;Spencer et al, 2006), therapists were concerned that it was not always enough to provide services that focused on building the capacity of teachers and changing the child's environment; rather, in certain situations, they felt that the provision of direct oneon-one interventions would have been more effective. Other authors have suggested that a continuum of services may be needed to manage the lengthy waitlists and varied needs of the school-aged population (Hanft & Shepherd, 2008;Hoyt-Hallett, Beckers, Enman, & Betuzzi, 2009). It is possible that there will be children whose needs cannot be fully managed via capacity building and environmental supports and who may require services outside of the classroom context.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns artigos demonstraram a tendência do uso de abordagens centradas na família (CUSICK; LANNIN; LOWE, 2007;FINGERHUT, 2009;GALVIN et al, 2010;HARRIS;DANIELS, 1996;HOYT-HALLETT et al, 2009;MAJNEMER;ROSENBLATT, 1994;STEWART et al, 2010;WALLEN et al, 2008). Segundo Galvin et al (2010) esta prática está baseada na idéia de que os pais são os especialistas quando se trata de sua criança e de que cada família é única.…”
Section: A Importância Dos Relatos Dos Pais Como Método Avaliativounclassified